Effect of Bushfire Exposure on the Properties of Lightweight Aggregate Masonry Blocks - Indunil Erandi Ariyaratne; Anthony Ariyanayagam; Mahen Mahendran (Fire, 2025)
This paper investigated the impact of repeated bushfire exposure on the properties of four different types of lightweight aggregate (i.e., expanded perlite, pumice, diatomite and expanded glass) masonry blocks for use in the external walls of bushfire shelters and buildings in bushfire-prone areas. First, the properties of cement, sand and lightweight aggregates were determined. Then, 15 different masonry block cement mixes—control, expanded perlite, pumice, diatomite and expanded glass mixes—were developed using the absolute volume method and lightweight aggregate cement mixes were developed by replacing sand in the control mix with lightweight aggregate on an equal volume basis. The test specimens cast included 100 mm diameter cylinders and 90 mm solid masonry blocks. Prior to bushfire exposure, the density and ambient compressive strength of the cement mixes were determined. Then, masonry blocks were exposed to bushfire flame zone conditions (BAL-FZ) for the first time and then for a second time (i.e., repeated exposure) and the effect of these exposures on the bushfire resistance and compressive strength (i.e., residual strength) of the masonry blocks was examined. The results obtained for the newly developed lightweight aggregate blocks were compared with those of the control block and two different commercially available solid blocks (i.e., Com 1 and Com 2). The control block recorded the highest temperature rises (69 and 84 °C), heating rates (1.26 and 1.47 °C/min) and compressive strength reductions (10.2 MPa) upon first-time and repeated bushfire exposure. The inclusion of lightweight aggregates in the masonry block mix lowered the temperature rises (between 17 and 61 °C) and heating rates (between 1.07 and 0.19 °C/min) on the ambient surface and also resulted in compressive strength reductions (between 3.2 and 9.0 MPa) during first-time and repeated bushfire exposure. Only the diatomite block (D60; block made with 60% diatomite aggregate) and commercial lightweight block (Com 2) remained within the interior temperature limits for bushfire shelters after both the first exposure and repeated exposure. However, only the D60 block satisfied the loadbearing strength requirement of 5 MPa even after repeated exposure. Therefore, considering the need to comply with the temperature limit on the interior surfaces of bushfire shelters during first-time and repeated exposure and to satisfy the loadbearing strength requirement of solid masonry units even after repeated bushfire exposure, the block made with 60% diatomite aggregate is recommended for use in the external walls of buildings in bushfire-prone areas.